1961
DOI: 10.1029/jz066i002p00351
|View full text |Cite
|
Sign up to set email alerts
|

Charged particles in the inner Van Allen radiation belt

Abstract: A nuclear emulsion stack was flown through the lower part of the inner Van Allen radiation belt a few days after the intense solar flares of July 10–16, 1959. The stack ‘looked out’ through a thin window on the mounting plate at the rear of the nose cone. Protons with incident energies down to 42 Mev were recorded. The total proton flux is about ⅓ that reported by Freden and White; the difference may be due to the lower peak altitude of the flight reported here. Above 100 Mev the proton spectrum is consistent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

1961
1961
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(6 citation statements)
references
References 16 publications
2
4
0
Order By: Relevance
“…The spectral shape we have measured is in good agreement with those measured in 1959-1960[Freden and White, 1959, 1960Armstrong, Harrison,Heckman, and Rosen, 1961;and Heckman and Armstrong, 1962], irrespective of the fact that these latter experiments were carried out near solar maximum (F::::: 200) at altitudes 460 < h .…”
Section: Energy Spectrumsupporting
confidence: 75%
“…The spectral shape we have measured is in good agreement with those measured in 1959-1960[Freden and White, 1959, 1960Armstrong, Harrison,Heckman, and Rosen, 1961;and Heckman and Armstrong, 1962], irrespective of the fact that these latter experiments were carried out near solar maximum (F::::: 200) at altitudes 460 < h .…”
Section: Energy Spectrumsupporting
confidence: 75%
“…Freden and White [1959] identified the penetrating component of the inner zone of the Van Allen belt as due to energetic protons and measured the energy spectrum of the protons of E • 75 Mev. Subsequent experimental work on Atlas rockets [Freden and White, 1960;Freden and White, 1962;Armstrong et al, 1961] has confirmed and extended this finding, and we now have a well-established proton energy spectrum at L •, 1.4, B •, 0.20, which is about apogee for these flights, for near solar maximum (Figure 1). The analysis of this spectrum [Freden and White, 1960] has shown conclusively that the protons are produced by neutron decay.…”
supporting
confidence: 70%
“…Neutrons produce radioactive isotopes, such as carbon 14 and tritium, by their capture in the atmosphere. In addition, the earth's neutron albedo is a source of geomagnetically trapped protons and electrons of can adequately explain the anomalously large flux of low-energy trapped protons which is observed at L •> 1.5 [Armstrong et al, 1961;Naugle and Kniy7en, 1961]. [1964] may be due to the Starfish explosion.)…”
Section: Introductionmentioning
confidence: 98%